East to Cathay : the silk road - Collins, Robert, 1924- (Trade routes series, 1971)
Describes the discovery and production of silk in ancient China, the exchange of goods, culture, and ideas which accompanied the silk caravans along the road from East to West, the experiences of the western traveler to the East, and the decline of the Chinese silk trade. Illustrated with contemporary prints and drawings.